Agricultural Implications of the Fukushima Nuclear Accident (III) After 7 Years - Nakanishi, Tomoko M.; O`Brien, Martin; Tanoi, Keitaro (Springer Nature, 2019)
This open access book presents the findings from on-site research into radioactive cesium contamination in various agricultural systems affected by the Fukushima Daiichi Nuclear Power Plant accident in March 2011. This third volume in the series reports on studies undertaken at contaminated sites such as farmland, forests, and marine and freshwater environments, with a particular focus on livestock, wild plants and mushrooms, crops, and marine products in those environments. It also provides additional data collected in the subsequent years to show how the radioactivity levels in agricultural products and their growing environments have changed with time and the route by which radioactive materials entered agricultural products as well as their movement between different components (e.g., soil, water, and trees) within an environmental system (e.g., forests). The book covers various topics, including radioactivity testing of food products; decontamination trials for rice and livestock production; the state of contamination in, trees, mushrooms, and timber; the dynamics of radioactivity distribution in paddy fields and upland forests; damage incurred by the forestry and fishery industries; and the change in consumers' attitudes. Chapter 19 introduces a real-time radioisotope imaging system, a pioneering technique to visualize the movement of cesium in soil and in plants. This is the only book to provide systematic data on the actual change of radioactivity, and as such is of great value to all researchers who wish to understand the effect of radioactive fallout on agriculture. In addition, it helps the general public to better understand the issues of radio-contamination in the environment. The project is ongoing; the research groups from the Graduate School of Agricultural and Life Sciences of The University of Tokyo continue their work in the field to further evaluate the long-term effects of the Fukushima accident.